The nuclear melatonin receptor RORα is a novel endogenous defender against myocardial ischemia/reperfusion injury. Issue 3 (16th February 2016) - He, Ben; Zhao, Yichao; Xu, Longwei; Gao, Lingchen; Su, Yuanyuan; Lin, Nan; Pu, Jun
Abstract: Circadian rhythm disruption or decrease in levels of circadian hormones such as melatonin increases ischemic heart disease risk. The nuclear melatonin receptors RORs are pivotally involved in circadian rhythm regulation and melatonin effects mediation. However, the functional roles of RORs in the heart have never been investigated and were therefore the subject of this study on myocardial ischemia/reperfusion (MI/R) injury pathogenesis. ROR α and ROR γ subtypes were detected in the adult mouse heart, and ROR α but not ROR γ was downregulated after MI/R. To determine the pathological consequence of MI/R‐induced reduction of ROR α, we subjected ROR α ‐deficient staggerer mice and wild‐type (WT) littermates to MI/R injury, resulting in significantly increased myocardial infarct size, myocardial apoptosis and exacerbated contractile dysfunction in the former. Mechanistically, ROR α deficiency promoted MI/R‐induced endoplasmic reticulum stress, mitochondrial impairments, and autophagy dysfunction. Moreover, ROR α deficiency augmented MI/R‐induced oxidative/nitrative stress. Given the emerging evidence of ROR α as an essential melatonin effects mediator, we further investigated the ROR α roles in melatonin‐exerted cardioprotection, in particular against MI/R injury, which was significantly attenuated in ROR α ‐deficient mice, but negligibly affected by cardiac‐specific silencing of ROR γ . Finally, to determine cell type‐specific effects of ROR α, we generated mice with cardiomyocyte‐specific ROR α overexpression and they were less vulnerable to MI/R injury. In summary, our study provides the first direct evidence that the nuclear melatonin receptor ROR α is a novel endogenous protective receptor against MI/R injury and an important mediator of melatonin‐exerted cardioprotection; melatonin‐ROR α axis signaling thus appears important in protection against ischemic heart injury.